Seaweed Falahmadahan / Faridah Tamma ... [et al.] - Tamma, Faridah; Mohammad, Fazilah; Hermanshah, Hermah Muhasaffia; Watinin, Norihan; Oyok, Norshuadah (2010)
Seaweed is one of the rare productions produced at Sabah. Rare people want to produce seaweed because they still do not realize the important and the uses of seaweed. The undeveloped of seaweed planting in Sabah brings us to make a seaweed production as our main goal for our business. ln fact, the Japanese consume more than 1 gram of seaweed per day on average. Seaweed cultivation is a thriving coastal industry in many Asian countries. Why do we choose Seaweed? ./ Due to the high demand and less competition . ./ A lot of things can be produced from seaweed . ./ High income . ./ Many benefits we can get from the seaweed. There are also some benefits we can get from the seaweed: ./ Overcomes poor digestion . ./ Aids in brain development . ./ Helps to prevent osteoporosis . ./ Beneficial for individuals that suffer from anemia and impotence . ./ Helps detoxify the body . ./ Increases metabolism . ./ Maintains hormonal balances. Besides, seaweed also can be converted as medicine, food and personal care product such as tooth paste ingredients and facial washer. The food industry also extracts ingredients for several different types of food additives from seaweed. Seaweed is used to retain water and gel food, especially confectionary products, meat and poultry items, desserts, and beverages. Some forms of seaweed are even used in various types of salad dressings or dietetic foods. Seaweed is even a preservative in meat and fish products, dairy products, and some types of baked goods. Therefore, by having five members to and guide from the Jabatan Perikanan sabah, we decide to open our business by using our company's name which is: SEA WEED F ALAHMADAHAN SDN. BHD. The seaweed refers to our main product, while the F ALAMADAHAN refer to Arabic mean which is 'falah' mean success. Actually, all the combination is referring to our company's members' name which are: Faridah, Fazilah, Hermah,Norshuadah, and Norihan. Due to the fact, Philippines are one of the biggest producers of seaweed, while Indonesia is one of the biggest exporters of seaweed and Malaysia is the best quality of seaweed production. So we decide to choose "Seaweed production, the best quality ever'' as our company motto. In fact, only Sabah has seaweed cultivation farm.